Theology in the context of world Christianity: how the global church is influencing the way we think about and discuss theology - Tennent, Timothy C. (Zondervan, 2007)
It's no secret that the center of Christianity has shifted from the West to the global South and East. While the truths of the Christian faith are universal, new contexts bring new questions, new understandings, and new expressions. What does this mean for theology? Is the Christian faith not only culturally translatable, but also theologically translatable? Timothy Tennent answers this question with a resounding yes. Theological reflection is alive and well in the majority world church, and these new perspectives need to be heard, considered, and brought into conversation with Western theologians. Global theology can make us aware of our own blind spots and biases. Because of its largely conservative stance, global theology has much to offer toward the revitalization of Western Christianity. Tennent examines traditional theological categories in conversation with theologians from across the globe, making this volume valuable for students, pastors, missionaries, and theologians alike.